Influence of crystal orientation on stretching induced void formation in poly(4‐methyl‐1‐pentene) investigated by in‐situ small‐angle and wide‐angle X‐ray scattering. Issue 6 (8th November 2021) - Yang, Qingqing; Liu, Xiang; Shi, Honghui; Zou, Lin; Cheng, Kaichang; Li, Taolin; Chang, Baobao; Liu, Chuntai; Shen, Changyu
Abstract: In this work, the void formation of poly(4‐methyl‐1‐pentene) (P4MP1) during solid‐state stretching was investigated by in‐situ small‐angle and wide‐angle X‐ray scattering. By controlling the heating temperature, P4MP1 specimens with different orientation degrees were obtained. The results showed that: (1) specimens with high orientation presented hard elastic deformation behavior. Before the voids were induced, a density decrease in the amorphous phase was detected due to the extension of chain network. Once voids were formed, their longitude direction was aligned perpendicular to the stretching direction. With the increase of crystal orientation, the volume fraction of voids was greatly enlarged; (2) specimen with random orientation showed cold drawing deformation. As the Hencky strain was larger than 0.13, the void scattering was strengthened in the vertical direction whereas weakened in the horizontal direction, indicating that the longitude direction of the voids was changed to the stretching direction. With further stretching, the length of the voids was enlarged and the orientation of the voids was enhanced, but the volume fraction of the voids was reduced slightly due to the collapse of small voids. After stretching, the length and width of the void evaluated from SEM were 382 and 81 nm. Abstract : For poly(4‐methyl‐1‐pentene) (P4MP1) with high orientation, an enlargement of the density contrast between crystalline phase and amorphous phase can be observed before voids were induced during solid‐state stretching. For P4MP1 with random orientation, the longitude direction of voids was perpendicular to the stretching direction once they were formed, and then transferred to stretching direction at larger deformation. In addition, two types of voids were observed concerning the existence of fibrils within the voids.